Dietary supplementation of soybean glycinin can alter the growth, carcass traits, blood biochemical indices, and meat quality of broilers - Osman, Ali (Poult Sci, 2020)
The current research aimed to estimate the effect of dietary supplementation with glycinin isolated from soybeans on the growth performance, carcass traits, and selected blood metabolites of broiler chicks. A total of 200 1-wk-old broiler chicks were administered diets without glycinin (control treatment) or diets supplemented with 3 concentrations of soy glycinin (0.5, 1.0, or 1.5 g/kg of feed) for 6 wk. At the end of the feeding period, body weight was significantly higher in broiler chicks with glycinin supplementation (P < 0.05 or 0.01). The best values for body weight and body weight gain were recorded in the groups fed diets supplemented with 0.5 and 1.0 g glycinin/kg feed. Feed conversion was significantly (P < 0.05) improved in broilers in the glycinin-supplemented groups during the 1 to 6 and 3 to 6 wk growth periods. The highest value of breast yield was observed in broiler chicks supplemented with glycinin at a concentration of 1.0 g/kg of feed. Water-holding capacity increased with increasing concentrations of glycinin in the feed, up to 1.0%. Serum creatinine and urea concentrations decreased gradually (P < 0.01) as the concentration of glycinin in the feed increased. Broiler chicks receiving increasing concentrations of glycinin exhibited significantly (P < 0.01) lower levels of serum triglycerides, total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol. All meat samples from broiler chicks supplemented with glycinin had significantly higher catalase activities. These data suggest that feeding broiler chicks diets supplemented with soy glycinin (0.5 to 1.5 g/kg of feed) can improve feed conversion, enhance body weight gain, and lower abdominal fat.